2021
DOI: 10.3390/chemengineering5030035
|View full text |Cite
|
Sign up to set email alerts
|

Coagulated Mineral Adsorbents for Dye Removal, and Their Process Intensification Using an Agitated Tubular Reactor (ATR)

Abstract: The aim of this study was to understand the efficacy of widely available minerals as dual-function adsorbers and weighter materials, for the removal of toxic azo-type textile dyes when combined with coprecipitation processes. Specifically, the adsorption of an anionic direct dye was measured on various mineral types with and without the secondary coagulation of iron hydroxide (‘FeOOH’) in both a bench-scale stirred tank, as well as an innovative agitated tubular reactor (ATR). Talc, calcite and modified benton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The samples were then left on a roller shaker (IKA, U.K.) for 12 h, after which the pH was checked once again, where it is believed that 12 h is far in excess of the time required for equilibrium adsorption to occur. Previous work by Taylor et al on similar doped TiO 2 and SHMP systems, indicated equilibrium was reached in tens of minutes, which would be consistent with other electrostatic-driven adsorption of large molecules on mineral systems …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were then left on a roller shaker (IKA, U.K.) for 12 h, after which the pH was checked once again, where it is believed that 12 h is far in excess of the time required for equilibrium adsorption to occur. Previous work by Taylor et al on similar doped TiO 2 and SHMP systems, indicated equilibrium was reached in tens of minutes, which would be consistent with other electrostatic-driven adsorption of large molecules on mineral systems …”
Section: Methodsmentioning
confidence: 99%
“…Previous work by Taylor et al 43 on similar doped TiO 2 and SHMP systems, indicated equilibrium was reached in tens of minutes, which would be consistent with other electrostatic-driven adsorption of large molecules on mineral systems. 44 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 The ATR is a commercially successful reactor in industries known to handle solid slurries and suspensions in addition to gas-liquid and solid-liquid-gas processes. [62][63][64][65][66][67] The unique tube-and-agitator design 68,69 has been proven to effectively circumvent pressure drops when connecting two or more reactors in series, thus enabling kilo-scale production with high throughput. Owing to these advantages, we decided to employ this scale-up tool for demonstrating the telescoped flow synthesis for the high-throughput production of DFNS.…”
Section: Telescoping the Continuous Flow Processes Of Emulsification ...mentioning
confidence: 99%
“…The only available water can be surface water from the river, lake, or pond that contains chemical pollutants and harmful microorganisms. Chemical pollutants can be removed by flocculation, the use of adsorbents (e.g., activated carbon), and filtration. Moreover, water disinfection is achieved by heating, filtration, and the use of disinfectants, such as hypochlorite and iodine. , The use of disinfectants has some advantages, including the ease of application to large or small quantities of water and no requirement for electricity or fuel sources. Nevertheless, appropriate control over the concentration of the disinfectants is required.…”
Section: Introductionmentioning
confidence: 99%